The content of differentiated teaching future engineers reading in English - Н. М. Тишко (Іноземні мови, 2016)
Inroduction. To improve students’ language proficiency level it’s necessary to develop professionally oriented English language reading competence. The requirements for the training of future engineers and professionals needs determine the development of professionally oriented English language reading competence as one of the practical aims of foreign language teaching in higher technical educational institutions. To implement it the content of teaching reading must be specified. Purpose. To determine components of professionally oriented English language reading competence and specify the content of differentiated instruction of English language reading of future engineers. Methods. Methodological literature has been analyzed to solve the problem mentioned above. Results. Professionally oriented English language reading competence is defined as the ability and willingness of a reader to find, single out, understand, and evaluate professional information and to use it practically in their professional activity. The main components of professionally oriented English language communicative competence are knowledge, subskills, skills and abilities. The knowledge of the specific types of functional English texts and linguistic knowledge (lexical and grammatical) necessary for future engineers to understand professional information is referred to declarative knowledge. Procedural knowledge is social and cultural knowledge which students acquire while reading authentic scientific texts. It serves not only as means of communication but also a means of spiritual enrichment through knowledge of culture studied. Lexical and grammatical subskills of reading which ensure accuracy and understanding of information have been defined. The skills in the English reading as reading skills to ensure the completeness of comprehension and skills to ensure the depth of understanding of the text have been classified. Reading for gist and intensive reading are regarded as the main types in differentiated instruction. The ability to response adequately and apply skills in the process of reading the information in future career is referred to communicative reading abilities. Having described components of professionally oriented English language reading competence, we determined the procedural aspect of the content of differentiated instruction of English language reading of future engineers. Objective aspect of the content of differentiated instruction of English language reading consists of four components. The first component includes areas of communication, appropriate situations, roles, communication goals, professional topics. Educational and professionally oriented topics are the main. The second component of the objective aspect of reading teaching content correlates with the need of development of linguistic and sociocultural competence of future engineers. The third component includes language material (lexical and grammatical). The fourth component includes strategies for mastering of professionally oriented English language reading competence. The following strategies have been singled out: Making Predictions, Wordbuilding, Making Inferences, Visualization, Making Summary, Grouping/classifying, Pattern Search. They help students with different language proficiency level to master professionally oriented English language reading competence. Conclusion. So, we have determined that one of the practical aims of teaching English in higher technical educational institutions is development of professionally oriented English language reading competence. The basic structural components of English reading competence of future engineers and the objective and procedural aspects of the content of differentiated instruction of English language reading of future engineers have been defined.